Global Burden of Neural Tube Defects, Risk Factors, and Prevention - E, Joseph; Flores, A L; Vellozzi, C; Valencia, D (Indian Journal of Community Health, 2014)
Neural tube defects (NTDs), serious birth defects of the brain and spine usually resulting in death or paralysis, affect an estimated 300,000 births each year worldwide. Although the majority of NTDs are preventable with adequate folic acid consumption during the preconception period and throughout the first few weeks of gestation, many populations, in particular those in low and middle resource settings, do not have access to fortified foods or vitamin supplements containing folic acid. Further, accurate birth defects surveillance data, which could help inform mandatory fortification and other NTD prevention initiatives, are lacking in many of these settings. The burden of birth defects in South East Asia is among the highest in the world. Expanding global neural tube defects prevention initiatives can support the achievement of the United Nations Millennium Development Goal 4 to reduce child mortality, a goal which many countries in South East Asia are currently not poised to reach, and the 63rd World Health Assembly Resolution on birth defects. More work is needed to develop and implement mandatory folic acid fortification policies, as well as supplementation programs in countries where the reach of fortification is limited.